Development and Usability Testing of a Novel Parking Assist System that Aids Other Drivers While Parking. (September 2018) - Mims, Lauren; Brooks, Johnell; Beckman, Mitch; Schwambach, Breno; Knizek, Robert; Uppalapati, Dheemanth; Jenkins, Casey; Venhovens, Paul; Melnrick, Ken; Karg, Jochen; Weber, Julian; Schulte, Joerg
Current parking assist systems are designed to aid the driver. This paper presents a new concept for a parking assist system that was designed to help other drivers. Sixteen participants participated in this usability study to evaluate the intuitiveness of the parking assist concept. The results showed that all of the participants understood the purpose of the system without any explanation. Participants provided valuable suggestions for future iterations. The majority of the participants would like to have this type of parking assist system on their own vehicle and would want to use it while parking. Future efforts are suggested prior to incorporating this concept on a production vehicle.